New South Wales annual vaccine-preventable disease report, 2013 - Alexander Rosewell; Paula Spokes; Robin Gilmour (World Health Organization Regional Office for the Western Pacific, 2015)
Aim: To describe the epidemiology of selected vaccine-preventable diseases in New South Wales, Australia for 2013. Methods: Data from the New South Wales Notifiable Conditions Information Management System were analysed by local health district of residence, age, Aboriginality, vaccination status and organism. Risk factor and vaccination status data were collected by public health units. Results: Pertussis notification rates in infants were low, and no infant pertussis deaths were reported. Despite a high number of imported measles cases, there was limited secondary transmission. The invasive meningococcal disease notification rate declined, and disease due to serogroup C remained low and stable. Conclusion: Vaccine-preventable diseases were relatively well controlled in New South Wales in 2013, with declining or stable notification rates in most diseases compared with the previous year.